Prevalence of cam and pincer deformities in the x-rays of asymptomatic individuals - Thier, Steffen; Fickert, Stefan (BioMed research international, 2017)
Objective. The presence of radiological signs of femoroacetabular impingement (FAI) is not necessarily associated with symptoms. Hence, the prevalence of cam and pincer deformities in the overall population may be underestimated. The purpose of this study was to screen an unselected cohort of people without hip symptoms for native radiological signs of cam and pincer deformities to determine their actual prevalence. Materials and Methods. 110 asymptomatic patients had AP pelvis X-rays and cross-table hip X-rays performed. We evaluated the images for the presence of cross-over signs and measured lateral center edge (LCE) angles, alpha angles (α-angles), and femoral offset ratios. Results. Positive cross-over signs were seen in 34%; LCE angles > 40° in 13%; and femoral offset ratios < 0.18 in 43%. In 41% of the patients, α-angles were >50°. Male patients showed significantly higher α-angles, lower offset ratios, and a higher prevalence of cross-over signs. In contrast, female patients had significantly higher LCE angles. Conclusion. According to our data, radiological signs of cam and pincer deformities are common in asymptomatic people. In clinical practice, patients presenting with hip pain and radiological signs of FAI should undergo further diagnostic evaluation. However, in asymptomatic patients, no further evaluation is recommended.